The repercussions of the COVID-19 pandemic for merchandise trade of the European Union with the Least Developed Countries (LDCs) - Mazur, Grzegorz (Skutki pandemii COVID-19 dla handlu Unii Europejskiej z najsłabiej rozwiniętymi państwami, 2021)
The COVID-19 pandemic has triggered unprecedented and multidimensional repercussions for the global trading system. In this context, special attention should be addressed to the group of the least developed countries (LDCs) with their vulnerable economies and export performance weighed down by structural deficiencies. The general aim of the paper was to identify the main changes in merchandise exports of LDCs to the European Union (EU) – being one of the most important export markets for those countries – in the aftermath of the pandemic. The methodology is based on descriptive statistics of merchandise exports from the least developed countries to the EU during the pandemic with reference to the previous pre-pandemic period. The analysis indicated a strong decrease (mostly recorded by exporters of energy and manufactured goods, less for suppliers of raw materials and food/agricultural products) in LDCs’ exports to the EU market. The latest trade statistics also revealed that countries with higher export concentration and those that have the ‘graduating status’ have been more affected by export falls than the group. This highlights the need for further structural changes in the least developed countries, cautious monitoring of the graduation mechanism and the influence of the pandemic on the socio-economic situation in the group.
Ekonomia XXI Wieku = Economics of the 21st Century, 2021, Nr 24, s. 89-100
Keywords: European Union; least developed countries; LDC; merchandise trade; exports; COVID-19; pandemic; Unia Europejska; najsłabiej rozwinięte państwa; eksport; pandemia